The Interplay of Self‐Certainty and Prosocial Development in the Transition from Late Adolescence to Emerging Adulthood. Issue 6 (November 2016) - Crocetti, Elisabetta; Moscatelli, Silvia; Van der Graaff, Jolien; Rubini, Monica; Meeus, Wim; Branje, Susan
Abstract: The transition from late adolescence to emerging adulthood is a period of the life span that offers young people the possibility to consolidate their self‐certainty and prosociality. Both aspects are of core importance for increasing personal and societal well‐being. The purpose of this longitudinal study was twofold: (i) to examine patterns of change and stability in self‐concept clarity and prosociality; and (ii) to unravel over time associations between these constructs in the transition from late adolescence to emerging adulthood. In addressing both aims, we explored the moderating effects of gender. Participants were 244 Dutch emerging adults (46% male; mean age at T1 = 16.73 years) who completed six waves of data collection (mean age at T6 = 22.7 years). Findings highlighted that (i) self‐concept clarity developed nonlinearly, with an initial decline from T1 to T2 followed by an increase thereafter, while prosociality increased linearly over time and both self‐concept clarity and prosociality were characterized by high rank‐order consistency; (ii) self‐concept clarity and prosociality were positively related over time, with the effect of prosociality on self‐concept clarity being stronger than the reciprocal effect of self‐concept clarity on prosociality. Gender differences were detected in mean levels of self‐concept clarity and prosociality (male participants reported higher self‐concept clarity and lower prosociality than female participants) but not in their developmental pathways nor in their reciprocal associations. Copyright © 2016 European Association of Personality Psychology